2017
DOI: 10.1016/j.archoralbio.2017.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing mandibular growth using three-dimensional imaging techniques and anatomic landmarks

Abstract: Objective To provide quantitative data on the multi-planar growth of the mandible, this study derived accurate linear and angular mandible measurements using landmarks on three dimensional (3D) mandible models. This novel method was used to quantify 3D mandibular growth and characterize the emergence of sexual dimorphism. Design Cross-sectional and longitudinal imaging data were obtained from a retrospective computed tomography (CT) database for 51 typically developing individuals between the ages of one and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
39
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 31 publications
10
39
1
2
Order By: Relevance
“…The dark red regions show positive growth (bone deposition) and dark blue regions show negative growth (bone resorption). The findings are consistent with previous studies based on 2D surface deformation [5] and landmarks [10]. …”
Section: Applicationsupporting
confidence: 93%
“…The dark red regions show positive growth (bone deposition) and dark blue regions show negative growth (bone resorption). The findings are consistent with previous studies based on 2D surface deformation [5] and landmarks [10]. …”
Section: Applicationsupporting
confidence: 93%
“…In our study, ANB angle was greater (5.75°) for the diagnosis of class II than what was previously reported (3.6°), suggesting a more posterior mandible position in younger children [23]. It has been reported that during puberty, the mandible experiences a pubertal growth spurt that can modify facial and sagittal skeletal relationship [11,16,32,33].…”
Section: Discussioncontrasting
confidence: 54%
“…Our study sample was homogeneous and more exhaustive than most previous studies, both in terms of the number of individuals included and of the age period studied (Hutchinson et al, ; Kelly et al, ; Smartt et al, ). Furthermore, the subdivision of the total study sample in subsamples according to the number of teeth apparent on the 3D models helped us to better correlate the highlighted morphological development of the mandible with the deciduous dentition development.…”
Section: Discussionmentioning
confidence: 99%
“…To present more reliable results, other authors proposed to characterize the mandible growth pattern with the definition of anatomical landmarks from which distances were computed (Hutchinson, L'AbbĂ©, & OettlĂ©, ; Kelly et al, ). With these approaches, only the modification of the mandible dimensions was investigated.…”
Section: Introductionmentioning
confidence: 99%